EFFECT OF USING AVOCADO, CHIA OIL AND THEIR MIXTURE IN BROILER DIETS ON PRODUCTIVE PERFORMANCE AND SOME CHEMICAL CHARACTERISTICS OF MEAT - A. A. Qassim,; L. K. Bandr,; F.M. Alkalani, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted in the field of the Poultry Research Station of the animal resources Department / office of Agricultural Research / Ministry of Agriculture from the period 4th April to16th May2021.This study was aimed to investigate the effect of using avocado and chia oil and their mixture in broiler diets on the final productive performance and meat cholesterol concentration and measuring meat oxidation indicators after storing it for 60 days. 300 one-day-old (Ross308) chicks were fed on diets that used avocado oil and chia with percentages of 0, 0.2, 0.4, 0.6%, respectively, and their mixture consisting of 0.0, 0.1, 0.2, 0.3 each of avocado and chia oil (50% avocado + 50% chia oil). The experiment included 10 treatments with 3 replicates for each treatment (10 birds/replicates). The results showed a high significant improvement (P < 0.01) in the productive performance of (average body weight, weight gain, feed intake and feed conversion ratio) for the interactions of avocado and chia oil mixture treatments with a usage rate of 0.6% compared with the interactions of the control treatment and the rest of the interactions of the used oils. The results showed a high significant decrease (P < 0.01) in the concentration of cholesterol, Malondialdehyde(MDA) and the peroxide value (PV) of fat for the treatments of interaction the oil mixture and the usage rates of 0.2, 0.4 and 0.6% in broiler's meat that stored for 60 days.